Lussa Wood 1: the late-glacial and early post-glacial occupation of Jura - Mercer, John (Proceedings of the Society of Antiquaries of Scotland, 1981)
NR 644874. A large quantity of microliths and three stone-built rings, perhaps cooking-places, represent occupation dated by 14C to the later 7th millennium bc; later material reflects activity on the site into Neolithic times. A R